2015
DOI: 10.5567/pharmacologia.2015.324.332
|View full text |Cite
|
Sign up to set email alerts
|

Dual Protective Effect of Cynodon dactylon in Epilepsy as Well as Depression

Abstract: Background and Objective: Depression and epilepsy are considered as the strongest predictor of poor quality of life. A complex relation has been established between the two conditions which suggest that the high co morbidity of depression and epilepsy is related to the existence of common neurobiologic and pathogenic mechanisms involved in them. Plants and their extracts are better choice to treat such type of diseases (in which treatment of one worsens the other), because of presence of antagonistic substance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Thus Suggests that ethanolic extract of Cynodon dactylon has anti-convulsant property and the verified its traditional use in epilepsy (Garg and Paliwal, 2011). Further investigation was done on the effect of ethanolic extract of Cynodon dactylon on epilepsy and depression in mice and The results possess promising antidepressant as well as antiepileptic activity which concluded that dual protective effect of Cynodon dactylon in epilepsy and depression is associated with diverse mechanism, namely GABAmimetic and 5-HT2 antagonistic action (Ingale and Gupta, 2015). Study which was performed to identify the antiepileptic activity of leaf extract on animal models resulted and suggested antiepileptic activity on animal models (Kaliyaperumal et al, 2013).…”
Section: Durva Grass In Epilepsymentioning
confidence: 88%
“…Thus Suggests that ethanolic extract of Cynodon dactylon has anti-convulsant property and the verified its traditional use in epilepsy (Garg and Paliwal, 2011). Further investigation was done on the effect of ethanolic extract of Cynodon dactylon on epilepsy and depression in mice and The results possess promising antidepressant as well as antiepileptic activity which concluded that dual protective effect of Cynodon dactylon in epilepsy and depression is associated with diverse mechanism, namely GABAmimetic and 5-HT2 antagonistic action (Ingale and Gupta, 2015). Study which was performed to identify the antiepileptic activity of leaf extract on animal models resulted and suggested antiepileptic activity on animal models (Kaliyaperumal et al, 2013).…”
Section: Durva Grass In Epilepsymentioning
confidence: 88%